Hemostasis Alterations and Placental Outcomes in Preeclampsia: Perubahan Hemostasis dan Kondisi Plasenta pada Preeclampsia - Adizova Sarvinoz Rizokulovna; Nosirova Zarnigor Jasur kizi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Pregnancy induces profound physiological changes in the hemostasis system, balancing procoagulant and fibrinolytic mechanisms to ensure maternal and fetal survival. Specific Background: Preeclampsia disrupts this balance, leading to hypercoagulation, endothelial dysfunction, and compromised placental circulation. Knowledge Gap: Despite numerous studies, the specific patterns of coagulation system alterations and their diagnostic value in preeclampsia remain incompletely characterized. Aims: This article aims to analyze the dynamic changes in coagulation and fibrinolysis during normal pregnancy and to compare them with the pathological shifts occurring in preeclampsia. Results: Findings demonstrate increased procoagulant activity, elevated D-dimer levels, reduced fibrinolysis, and decreased antithrombin III activity in preeclampsia. These changes contribute to placental insufficiency, fetal growth restriction, and heightened maternal risk of thrombohemorrhagic complications. Novelty: The study highlights the prognostic importance of D-dimer levels and platelet indices as accessible markers to monitor hemostasis dysfunction in preeclampsia. Implications: Early identification of coagulation markers offers prospects for improving diagnostic precision, guiding therapeutic strategies, and preventing severe maternal-fetal complications in preeclampsia. Highlight: Altered coagulation and fibrinolysis in preeclampsia drive maternal and fetal risks. D-dimer and platelet indices emerge as practical prognostic markers. Early detection of hemostasis dysfunction enables better clinical outcomes. Keywords: Preeclampsia, Coagulation Cascade, Fibrinolysis, D-Dimer, Hemostasis